ANALISIS LIKUIDITAS UNTUK MENGUKUR PERPUTARAN MODAL KERJA PADA PT. MARINAL INDOPRIMA KOPEDI SUMENEP - Kristiana, Kristiana (Fakultas Ekonomi, Program Studi Akuntansi, 2018)
The purpose of this research is to know Liquidity Analysis to measure Work Capital Turnover At PT. Marinal Indoprima Kopedi Sumenep. This descriptive research using secondary data from 2014-2016 in the form of report of cost of goods production, income statement, and balance sheet. While the data collection techniques used are literature and documentation. Data analysis technique used is comparative analysis of financial statements is by comparing the financial statements for two or more periods. Based on the result of research indicate that liquidity of PT. Marinal Indoprima from 2014-2016 stability from year to year. This is because current assets are sufficient to pay off their short-term liabilities. At Working Capital from 2014-2016 continues to increase. In addition, in terms of working capital turnover from year to year shows quite effective.